Talent development at the Voice of Holland: Identifying and Developing Singing Talents to Grow into Professional Performers - Manuel, Karin (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2023)
There is a lack of research into talent identification and talent development in the field of performing arts. The Voice of Holland (TVOH) has been the subject of a longitudinal empirical study as a good example of a setting for talent identification and talent development in this field. The study involved a literature review on talent approaches, talent identification, talent development, and performance. The study sought answers to the question how coaches at TVOH identify the singing talents of participants and contribute to develop these talents to a higher level of performance necessary for growth into a professional performer. Data were collected by desk research, participative observations, and qualitative interviews. The study revealed that talent identification and talent development intertwine, transformational coaching is part of performance coaching, and the preparation of talents in the field of the performing arts benefits a more integrated approach on talent development to enhance the overall performance needed to grow into a professional performer. Although the findings and conclusions are context specific for TVOH, they might be useful for teachers, coaches, and talents in the field of the performing arts and anyone else interested in the education and preparation of talents in general.